Basic regulatory science behind drug substance and drug product specifications of monoclonal antibodies and other protein therapeutics - Patanachai K. Limpikirati; Sorrayut Mongkoltipparat; Thinnaphat Denchaipradit; Nathathai Siwasophonpong; Wudthipong Pornnopparat; Parawan Ramanandana; Phumrapee Pianpaktr; Songsak Tongchusak; Maoxin Tim Tian; Trairak Pisitkun (Elsevier, 2024)
In this review, we focus on providing basics and examples for each component of the protein therapeutic specifications to interested pharmacists and biopharmaceutical scientists with a goal to strengthen understanding in regulatory science and compliance. Pharmaceutical specifications comprise a list of important quality attributes for testing, references to use for test procedures, and appropriate acceptance criteria for the tests, and they are set up to ensure that when a drug product is administered to a patient, its intended therapeutic benefits and safety can be rendered appropriately. Conformance of drug substance or drug product to the specifications is achieved by testing an article according to the listed tests and analytical methods and obtaining test results that meet the acceptance criteria. Quality attributes are chosen to be tested based on their quality risk, and consideration should be given to the merit of the analytical methods which are associated with the acceptance criteria of the specifications. Acceptance criteria are set forth primarily based on efficacy and safety profiles, with an increasing attention noted for patient-centric specifications. Discussed in this work are related guidelines that support the biopharmaceutical specification setting, how to set the acceptance criteria, and examples of the quality attributes and the analytical methods from 60 articles and 23 pharmacopeial monographs. Outlooks are also explored on process analytical technologies and other orthogonal tools which are on-trend in biopharmaceutical characterization and quality control.